Elastic properties and FTIR investigation of 80TeO₂-(20-x)ZnO-xFe₂O₃ and (80-x)TeO₂-20PbO-xWO₃ tellurite glass systems / Azianty Saroni - Saroni, Azianty (2013)
In this work, the effects of Fe₂O₃ addition in 80TeO₂-(20-x)ZnO-xFe₂O₃ and WO₃ addition in (80-x)TeO₂-20PbO-xWO₃ glasses were studied. The glasses were prepared by the melt-quenching method. Elastic and structural properties of the glasses were investigated by measuring both longitudinal and shear velocities using the pulse-echo overlap method at 5MHz and Fourier Transform Infrared (FTIR) spectroscopy, respectively. For the 80TeO₂-(20-Ac)ZnO-xFe₂O₃ (x = 0-15 mol%) glass, both longitudinal and shear velocities showed a large increase at x = 5 mol% before a smaller increase for x > 5 mol%. The initial large increases in shear and longitudinal velocity and related elastic moduli observed at x = 5 mol% are suggested to be due to structural modification which enhances rigidity of the glass network. FTIR analysis showed increase in bridging oxygen (BO) as indicated by the relative intensity of the TeO₄ assigned peaks and increase in intensity of FeO₆ assigned peak (~451 cm⁻¹) which indicates that Fe acts as a modifier in the glass network. For the ((80-x)TeO₂-20PbO-xWO₃ (x = 0-20 mol%) glass, both longitudinal modulus (L) and shear modulus (G) showed a decrease at x = 5 mol% followed by a large and almost linear increase for x > 5 mol%. FTIR analysis showed increase in intensity of TeO₃ assigned peak concurrent with the decrease in intensity of TeO₄ asssigned peak at x = 5 mol% which indicates an increase in number of non-bridging oxygens (NBO) and a decrease in number of bridging oxygens (BO), respectively. Quantitative analysis based on bulk compression and ring deformation models showed a decrease in kbc/kc ratio for both studied glasses infers that the glass system became a relatively more open 3D network as Fe₂O₃ and WO₃ was increased.